On guilt the force shaping character, history, and culture - Carroll, John 1944- (Routledge, 2020)
"This book explores the nature of guilt, shedding light on how the modern West came increasingly to understand it as 'the most terrible sickness'. It traces the psychological origins of guilt in each person's family, and demonstrates the historical rise of guilt in parallel with civilization. It examines the modern predicament: the difficulty of finding explanations for guilt in a secular, post-church society - and the possibility of relief from its curse, while channeling it into a fulfilling life. As such it will appeal to those with interests in sociology, psychology, psychiatry, cultural studies, cultural history, and anthropology"--
Keywords: Guilt; Guilt and culture; Civilization / History